Overview of Resilience: Study on BIDIK-MISI Scholarship Recipient College Students - Wahyudi, Amien; Suardimana, Siti Partini (Universitas Muhammadiyah Metro, 2018)
This study aims to determine the resilience of BIDIK MISI scholarship recipients. The method used in this research is qualitative method with a case study approach. Respondents were BIDIK MISI scholarship recipients by two students who have criteria(1) Student BIDIK MISI scholarship recipients, (2) have a GPA of 3.50 ± ≥ (3) active in student organizations as well as a proven record in the field of scientific work. The data was collected using interviews, informal interviews, and observation. The data obtained in this study later in descriptive. The data is then analyzed, the detailed answer then coded and identified to get the themes in the study. Resilience students receiving the viewfinder can be seen from the aspect of the mission, meaning fullness, Perseverance, patience, self-reliance, and existential aloneness. Students receiving BIDIK MISI was able to detach himself from the family and economic stressors that students are receiving a personal mission view finder that has a clear purpose in life.